ROLE OF FINANCIAL RESOURCE MOBILIZATION IN ENHANCING SUSTAINABLE ACCESS TO WATER IN ARID AND SEMI ARID AREAS IN KENYA (International Journal of Innovative Technologies in Economy, 2023)
The aim of this study was to establish the role played by financial resource mobilization in enhancing sustainable access to water in arid and semi arid areas in Kenya. Access to water is instrumental in driving economic development and stimulating the productivity of a country’s population. Lack of safe and clean water has been a major challenge to most of the Kenyan households, especially those in arid and semi arid areas. Ensuring adequate financial resources would be essential to stimulate implementation of key programmes that ensure sustainable access to water. This study specifically sought to assess the role played by resource mobilization skills, government funding, external funding sources, budgeting and planning and accountable use of financial resources on the sustainable access to water in arid and semi arid areas in Kenya. Using a crosssectional research approach, the study surveyed 20 respondents drawn from two main water development agencies in Kenya. A structured questionnaire was used to collect the primary data. The data was analysed using descriptive statistics and findings presented in tables. The results reveled that financial resource mobilization skills were essential in promoting sustainable access to water. The study further revealed that government funding from both national and county governments were essential in ensuring implementation of water programmes aimed at enhancing access to water. External sources of funds were also found to be critical in enhancing sustainable access to water. The study recommends that the government should increase allocations to the water agencies so as to promote the implementation of key programmes for enhancing sustainable access to water in arid and semi-arid areas. Accountability should also be upheld so as to ensure that the financial resources are responsibly utilized for sustainable access to water in the arid and semi arid areas.